Decision Support System For Determining the Best College High Private Using Topsis Method - Lestari, Yuyun Dwi; Mardiana, Mardiana (Sinkron : Jurnal dan Penelitian Teknik Informatika, 2020)
In this study, the Best Private Universities in Medan will be discussed with the TOPSIS method (Techniques for Other References with Similarities to Solutions). TOPSIS is one method of Decision Support Systems that is used to accept decisions that have many criteria. The general objective of this study is to use the TOPSIS method which is expected to be able to provide optimal results in determining the best universities. And specific targets of this study can provide estimates or indicators that can be used by Universities in Medan in determining whether the College is the best or not. The criteria used in this study were Institutional, Student Activities, Lecturer HR, Research and Community Service, and Innovation. In the future these criteria can be added according to the needs and requirements provided by the Ministry of Research, Technology and Higher Education. By applying the TOPSIS Method to Decision Supporters in the selection of the Best Private Universities in Medan City can provide optimal results based on the criteria and weighting that has been determined.